2020
DOI: 10.1007/s12144-020-01132-1
|View full text |Cite
|
Sign up to set email alerts
|

Variables protecting mental health in the Spanish population affected by the COVID-19 pandemic

Abstract: The pandemic produced by COVID-19 can lead the population to suffer serious psychological disorders. However, there are several psychosocial variables that can enhance resilient outcomes in adverse situations. The aim would be to establish the level of resilience of the general Spanish population exposed to a traumatic situation by the COVID-19 in order to identify which protective factors predict resilient outcomes. 1227 homebound people (863–70.3% women), aged 18–73 years (M = 28.10; SD = 12.88) reported on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 81 publications
(103 reference statements)
0
25
0
3
Order By: Relevance
“…More importantly, the CMA results highlighted that only selected items of the PTGI (i.e., 12 items) described by Weiss and Berger (2006) should be used to evaluate the PTG with the current participants in the context of COVID-19. Interestingly, although some other researchers also recommended the short versions of the PTGI (e.g., 10- or 12-item) ad hoc COVID-19, their proposals were mainly due to the time consumption issue instead of empirical evidence (e.g., Robles-Bello, Sánchez-Teruel, & Naranjo, 2020 ; Vazquez et al, 2021 ). The current results bridged this research gap.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, the CMA results highlighted that only selected items of the PTGI (i.e., 12 items) described by Weiss and Berger (2006) should be used to evaluate the PTG with the current participants in the context of COVID-19. Interestingly, although some other researchers also recommended the short versions of the PTGI (e.g., 10- or 12-item) ad hoc COVID-19, their proposals were mainly due to the time consumption issue instead of empirical evidence (e.g., Robles-Bello, Sánchez-Teruel, & Naranjo, 2020 ; Vazquez et al, 2021 ). The current results bridged this research gap.…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted in Saudi Arabia also demonstrated the importance of educational level and health awareness in promoting adherence to safety measures (Al-Hanawi et al, 2020). Moreover, psychological stress and resilience mechanisms might play an important role, especially during prolonged quarantine (Robles-Bello et al, 2020;Wang et al, 2020). Most of the abovementioned studies were limited by the lack of a theoretical framework that could interpret their findings within their respective sociodemographic contexts.…”
Section: Introductionmentioning
confidence: 99%
“…This is the case of resilience, which can be understood as the ability to adaptively coping or bouncing back from adversities (e.g., Fletcher and Sarkar, 2013) and dispositional optimism (i.e., the tendency to think in terms of future positive outcomes; e.g., Carver and Scheier, 2014). Both variables have been shown positively associated with mental well-being (e.g., Kimhi et al, 2020;Robles-Bello et al, 2020) and preventive behaviors (e.g., Pasion et al, 2020;Yildirim and Arslan, 2020). Against this backdrop, the aim of the present study is to build upon the HBM to deepen such associations in the particular context of the lockdown imposed in Spain during the first COVID-19 wave.…”
Section: Introductionmentioning
confidence: 99%